PERLINDUNGAN HUKUM TERHADAP KONSUMEN MUSLIM DALAM MENDAPATKAN JAMINAN HALAL PADA APLIKASI LAYANAN FOOD DELIVERY - Meirina Dewi Pratiwi; Sakinah Agustina (Fakultas Hukum Universitas IBA Palembang, 2023)
ABSTRACT The existence of products that have not been halal certified has resulted in consumers, especially Muslim consumers, finding it difficult to distinguish which products are truly halal and can be consumed in accordance with Islamic law from products that are not haram. advances in science and technology which are the driving force for the productivity and efficiency of producers of the goods or services they produce in order to achieve business targets. Muslim consumers in Indonesia have received protection for the products they will consume, both food and beverages, through regulations written in law number 34 of 2014 concerning Halal Product Guarantee. From the things mentioned above, how is the legal protection for Muslim consumers in obtaining halal guarantees for food delivery service applications? The research in this paper is normative juridical research. To achieve its objectives, the consumer protection law sub-system cannot be separated from other legal sub-systems. for example with health law. For business actors or producers, they need to realize that the survival of their business is very dependent on consumers. For this reason, they have an obligation to produce goods and services as good and as safe as possible and try to provide satisfaction to consumers.